Body, Soul and Spirit. Henri de Lubac’s Vision of Tripartite Anthropology - Persidok, Andrzej (Verbum Vitae, 2022)
The article discusses “tripartite anthropology” developed by Henri de Lubac, with particular emphasis on the concept of the “spirit”. The analysis carried out herein aims firstly to reconstruct a coherent anthropological vision from the fragments scattered in various works of this classic 20th-century theologian. Secondly, it aims to show that the vision of “tripartite anthropology” is still a valid response to contemporary attempts to reduce human existence to the body and psyche. In this context, particularly important is the paradoxical nature of the “spirit,” as shown in this study, which is understood as the sphere of human openness to transcendence: it represents both the coping and the center of human nature. Bringing to light this dual role of the “spirit-pneuma” within de Lubac’s theological anthropology is one of the significant results of the analysis presented in the text.